2019
DOI: 10.1097/md.0000000000017777
|View full text |Cite
|
Sign up to set email alerts
|

Phlegmonous gastritis in a patient with mixed-phenotype acute leukemia in the neutropenia phase during chemotherapy

Abstract: Rationale:Phlegmonous gastritis is a rare bacterial infection of the gastric wall with high mortality. However, diagnosis of phlegmonous gastritis is difficult and standard treatment remains unestablished.Patient concerns:We report a 33-year-old male patient with mixed-phenotype acute leukemia who developed acute phlegmonous gastritis during the neutropenia phase on induction chemotherapy and was successfully treated.Diagnoses:The patient was diagnosed with phlegmonous gastritis, which might be caused by Steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…In general, hematological malignancies tend to be accompanied by a decrease in immunocompetence, and myelosuppression by the administration of anticancer drugs further promotes immunodeficiency. There have been 6 reports of patients with hematological malignancies who developed PG during the neutropenic phase after the administration of anticancer drugs, including 1 of our previous patients[ 9 - 14 ]. Table 2 summarizes the clinical features of a total of 7 patients, including the patient experienced this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, hematological malignancies tend to be accompanied by a decrease in immunocompetence, and myelosuppression by the administration of anticancer drugs further promotes immunodeficiency. There have been 6 reports of patients with hematological malignancies who developed PG during the neutropenic phase after the administration of anticancer drugs, including 1 of our previous patients[ 9 - 14 ]. Table 2 summarizes the clinical features of a total of 7 patients, including the patient experienced this time.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that vonoprazan, a potassium-competitive acid blocker used in this patient, showed a stronger gastric acid secretion inhibitory effect than proton pump inhibitor and induced a stronger change in the composition of the intestinal flora[ 17 ]. Shi et al [ 14 ] expressed concern that the use of gastric acid secretion inhibitors increases the bacterial abundance in the gastric juice and thus may result in risk for the development of PG. Currently, there are few patients with PG with or without hematological malignancies, and scientific evidence is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous bacterial organisms have been implicated as the most common pathogens; however, the Streptococcus genus accounts for approximately 67-75% of cases [1]. Diagnosis is difficult and requires a combination of clinical presentation, imaging, bacterial culture, and pathology [3].There is currently no consensus on the proper management of PG; however, mortality rates have been reported as high as 27% [1][2][3]. Therefore, early recognition and treatment with antibiotics is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…The patient had pallor and moderate splenomegaly on clinical examination. His complete blood count (CBC) revealed a hemoglobin level of 78 g/L, platelet count of 9×10 9 /L, and white blood cell (WBC) count of 7.2×10 9 /L with 63% circulating blasts. Bone marrow aspirate showed 94% blasts.…”
mentioning
confidence: 99%
“…TRALI and necrotizing enterocolitis were thought to be fungal infections and acute phlegmonous gastritis. These pathologies are rapidly fatal and require prompt measures for management [ 8 , 9 ]. Autopsy revealed different morphological subtypes of fungal species, which may require a different therapeutic approach [ 8 ].…”
mentioning
confidence: 99%